An integrated toolkit for equality in daily urban mobility in Saudi Arabia: advancing gender mobility indicators - Amira Asaad; Asmaa Ibrahim; Tarek Abou El Seoud; Nancy M. Abdel-Moneim (Renewable Energy and Sustainable Development, 2024)
The significance of unimpeded mobility in everyday activities, including commuting, shopping, and social interactions, cannot be overstated. However, many persons, particularly women, face challenges that restrict their ability to move freely because of various circumstances, such as gender-related concerns and socio-economic inequalities. The absence of a well-defined framework and comprehensive indicators for addressing gender-related mobility concerns is a notable challenge in the Kingdom of Saudi Arabia (KSA) and other similar regions. This article comprehensively analyses several mobility indicators and dimensions from diverse literature, specifically emphasizing their applicability in promoting gender equality in urban mobility within the Kingdom of Saudi Arabia (KSA). A comprehensive framework is established by rigorous analysis and comparison, taking inspiration from the "Four A's" concept introduced by the World Bank in 2020. The approach offers valuable help in navigating the complex interplay between gender dynamics and urban mobility. The comparison underscores the significance of including privacy, Security, availability, and diversity of public transportation indicators in the toolkit. This inclusion is necessary to address the unique requirements, safety considerations, and cultural contexts of women when designing public transportation systems. The primary objective of these initiatives is to advance gender equality in the context of urban transportation in Saudi Arabia.   Received: 20 December 2023 Accepted: 03 March 2024 Published: 28 March 2024